Psychological Vitality and its relationship to Emotional Blackmail in a Sample of Husbands who are Emotionally Separated from their Wives - Al-Shelash, Omar Sulaiman (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to identify the relationship between psychological vitality and emotional blackmail among husbands who are emotionally separated from their wives. It also aimed to identify the differences between husbands in both psychological vitality and emotional blackmail, according to the age stage and educational qualification. Of (180) of the emotionally separated husbands from their wives, the study used the measures of psychological vitality and emotional blackmail (prepared by the researcher), and the results indicated that there is an inverse correlation between each of the psychological vitality and emotional blackmail of the husbands of the study sample, as it was found that there are statistically significant differences between the husbands The study sample was on the psychological vitality scale in favor of the lower age group and the higher educational qualification, and there were statistically significant differences between spouses. The study sample was on the emotional blackmail scale in favor of the older age group and the lowest educational qualification, The researcher presented a set of recommendations that include working to provide counseling programs and training courses for young people who are about to marry to learn how to confront family problems and maintain marital stability. The study also recommends providing psychological counseling centers with counseling courses and programs to develop psychological vitality for youth, and counseling programs to raise awareness of the risks Emotional Blackmail, and how to overcome it in young people.